Spatial and temporal occurrence of N-nitrosamines in seven drinking water supply systems - Brisson, I.; Levallois, P.; Tremblay, H.; Sérodes, J.; Deblois, C.; Charrois, Jeffrey; Taguchi, V.; Boyd, J.; Li, X.; Rodriguez, M. (Springer Netherlands, 2013)
The spatiotemporal presence of eight N-nitrosamines in the water of seven supply systems in Quebec considered to be susceptible to these emerging disinfection by-products was evaluated. This is the first study on the presence of N-nitrosamines in drinking water utilities in Quebec. Seven sampling campaigns were carried out at several sampling points in each of the systems over a period of 1 year. The results show that N-nitrosamines, primarily N-nitrosodimethylamine(NDMA), were not commonly detected in the water of the facilities under study (10 % of samples). The concentrations measured were lower than those reported in recent North American studies. None of the 195 samples taken exceeded the Ontario standard of 9 ng/L for NDMA (maximum value observed of 3.3 ng/L). N-nitrosomethylethylamine and N-nitrosopiperidine were detected once, with concentrations of 3.7 and 6.0 ng/L, respectively. Chloramination was identified as being the main risk factor regarding the presence of N-nitrosamines, but water quality and some operating parameters, in particular disinfectant residual, also seem to be related to their presence. NDMA concentrations at the end of the distribution systems were generally higher than water leaving the plant. No seasonal trends were observed for the formation of N-nitrosamines in the investigated supply systems. Finally, an association between the presence of N-nitrosamines and the levels of trihalomethanes and haloacetic acids was observed in some facilities.